2022
DOI: 10.1186/s12889-021-12454-5
|View full text |Cite
|
Sign up to set email alerts
|

A survey of depression and anxiety disorders in urban and rural Suriname

Abstract: Background Suriname is a Low-middle income country consisting of diverse population groups. Epidemiological studies concerning mental disorders like depression and anxiety had not been conducted until 2015. The treatment gap for mental disorders in Low and middle-income countries (LMICs) may reach 76-80% as treatment is not always readily available. In this study, we estimate and compare the prevalence of potential cases of depression and anxiety, as well as the size of the treatment gap in a r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Secondly, compared with residents living in areas with high urbanization, those living in areas with lower urbanization have less awareness of depression and its severity, as rural residents may have limited access to sources of health information ( Chen et al, 2019 ). Lack of awareness of depression and its symptoms could affect rural residents willingness to receive diagnosis or treatment, resulting in low utilization of basic public health services ( Jadnanansing et al, 2022 ; Li et al, 2011 ; Phillips et al, 2009 ). Thus, urbanization can provide opportunities to protect health, especially for people with depression, such as better living conditions, dissemination of better health knowledge, and improved access to health care ( Purtle et al, 2019 ; van der Wal et al, 2021 ; Yang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, compared with residents living in areas with high urbanization, those living in areas with lower urbanization have less awareness of depression and its severity, as rural residents may have limited access to sources of health information ( Chen et al, 2019 ). Lack of awareness of depression and its symptoms could affect rural residents willingness to receive diagnosis or treatment, resulting in low utilization of basic public health services ( Jadnanansing et al, 2022 ; Li et al, 2011 ; Phillips et al, 2009 ). Thus, urbanization can provide opportunities to protect health, especially for people with depression, such as better living conditions, dissemination of better health knowledge, and improved access to health care ( Purtle et al, 2019 ; van der Wal et al, 2021 ; Yang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that with proper advertisement it is possible to apply eHealth modules for mental disorders in LMIC. This is favorable since recent surveys have shown a significantly high treatment gap for alcohol abuse disorders [12] and depression and anxiety [13]. The program fully adheres to the WHO Mental Health Gap Action Program.…”
Section: Comparison With Prior Workmentioning
confidence: 98%
“…Web-based mental health for the Surinamese community is made possible through the eHealth.sr website [11] hosted by the PCS. This website was developed in collaboration with Arkin Mental Health Care in the context of a survey research project on the prevalence and treatment gap for substance use disorders, depression, and anxiety among the population of the Surinamese districts Nickerie and Paramaribo [12,13]. Respondents in this survey project who scored above cutoff points for alcohol abuse, depression, or anxiety were referred to the eHealth.sr website.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Studies on China have shown that rural residents have significantly higher depressive symptoms than urban residents, 23 and that women among rural students are at higher risk of experiencing depression. 24 Especially in low- and middle-income countries, women with low education, widows, divorced and unemployed women are at higher risk of depression, 25 and urban-rural disparities in depressive symptoms are concentrated in the group of unpartnered women. 26 However, it has also been found that rural residence reduces the risk of major depressive disorder and is more protective for young women than young men.…”
Section: Introductionmentioning
confidence: 99%